Tape‐Assisted Residual Layer‐Free One‐Step Nanoimprinting of High‐Index Hybrid Polymer for Optical Loss‐Suppressed Metasurfaces - Yujin Park; Joohoon Kim; Younghwan Yang; Dong Kyo Oh; Hyunjung Kang; Hongyoon Kim; Junsuk Rho (Advanced Science)
Abstract The commercialization of metasurfaces is crucial for real‐world applications such as wearable sensors, pigment‐free color pixels, and augmented and virtual reality devices. Nanoparticle‐embedded resin‐based nanoimprint lithography (PER‐NIL) has shown itself to be a low‐cost, high‐throughput manufacturing method enabling the replication of high‐index nanostructures. It has been extensively integrated into the fabrication of hologram metasurfaces, metalenses, and sensors due to its procedural simplicity. Most research on PER‐NIL has been limited to exploring appropriate materials to enhance the efficiency of imprinted metasurfaces, but the intrinsic issue of PER‐NIL lies in the high‐index residual layer remaining on the substrate. This high‐index residual layer generates undesired noise, limiting the efficiency and functionality of imprinted metasurfaces. Despite the need for the removal of the residual layer, it has never been experimentally achieved owing to the different etching rates between the nanoparticles and resin. Here, a new methodology named tape‐assisted PER‐NIL is proposed, achieving one‐step removal of the residual layer using a tape. This novel method enables the replication of residual layer‐free, high‐index metasurfaces. As a result, imprinted residual layer‐free metasurfaces prove their potential in high‐purity dielectric structural colorations by achieving a sharp reflectance peak unattainable with conventional NIL, and in vivid hologram metasurfaces by covering a full 2π phase without unwanted scattering.